CARING FOR OTHERS: CHALLENGES AND POSSIBILITIES - de la Cuesta Benjumea, Carmen (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Caregiving is a human activity with a professional component. Nevertheless it is regarded as the core of nursing. Thus it is surprising to see how care giving is slipping away from nursing hands, sometimes into the hands of nursing auxiliaries and patient’s relatives or friends. This paper explores the nature of care giving and the phenomenon of family care, its contribution and place in the health care system, stressing that family care giving is becoming a family issue with increasingly relevance and weight. Research studies have shown that family caregivers need both technical and emotional support which ought to be regarded as clients and not just means of care giving. Professional nurses could prepare and support caregivers to manage the different stages of the relative’s disease and its changes. Nurses could also anticipate crises and detect situations of poor care giving.